4 good reasons why - Butler, G. ; Bourne, F. ; Green, J. W. ; Gowridge, T. ; Whitehead, A. S. ; Abell, William H. ; Pickard, J. G.; Corah, John Reginald
1938-10 1938 1930s 12 pages All through the Day All through the Night The Royal Infirmary Casualty Department gives unfailing service. Built in 1901, reconstructed in 1925, it comprises a Waiting Room, Surgery, Doctor's Room, Theatre, and four Examination Cubicles — accommodation which is inadequate to deal with the present accident needs of nearly 2,300 attendances weekiy. Contrary to general belief, the majority of casualties are not the result of motor accidents. Injuries at home and at work make the biggest demands on the Department, as the following figures for 1937 clearly show:— Home and Street Accidents where no motor vehicle was involved 10,152 Works Accidents 6,490 Persons Injured by Motor Vehicles 1,027 Persons Injured by Pedal Cycles 859 Persons Injured by Tramcars or Horse-drawn Vehicles 79 Other urgent medical and surgical cases 6,316 24,923 [photograph] Present Casualty Department. 292/842/2/106